KOLABORASI STRATEGI DIGITAL MARKETING DALAM MENINGKATKAN KINERJA PEMASARAN USAHA KULINER DI KOTA MALANG - Alfira Rosadian (Jurnal Pijar, 2023)
This study aims to analyze the effectiveness of business collaboration through digital marketing strategies including social media marketing (SMM), influencer marketing and video marketing as digital marketing strategies in supporting the marketing performance of culinary businesses in Malang City. The research method uses a triangulation qualitative study. The results of the study conclude that the role of digital marketing collaboration through social media marketing strategies, video marketing and influencer marketing has a positive impact on marketing performance, both directly and indirectly. The main target of the brand is to get the maximum engagement from the audience for the content. These three strategies provide feedback in the form of audience engagement as measured by the engagement rate for each content. Although not many achieve sales targets directly. However, a high engagement rate will give birth to potential buyers. This stage is the process in achieving optimal marketing performance. Other findings conclude that the main strategy that is suitable in supporting culinary businesses is social media marketing, especially supported by video media as an intervening. The right video content can provide more information for the audience regarding culinary brand details such as raw materials, menus and variants, serving methods, food or drink textures and so on. On the other hand, collaborative marketing using influencers is very supportive for new brands, this is necessary in an effort to create a brand image.